The State as A Cultural Prefect Based on Islamic Political Principles - Mukhtar, Mukhtar (Jurnal Ilmiah Teunuleh, 2023)
The state, as a cultural product, plays a crucial role in translating Islamic political principles into social governance. Islam is not only a religion concerned with worship but also offers comprehensive guidance on human interactions and governance (muamalah). This duality makes the existence of the state and political power an essential aspect of Islamic teachings. Despite ongoing debates between scholars regarding the inseparability of Islam and politics, this study argues that the state, based on Islamic political principles, is indispensable for realizing justice, welfare, and equality in society. This research employs a qualitative literature review method, analyzing classical and contemporary Islamic political thought through philosophical, historical, and socio-political lenses. Key works from seminal thinkers such as Shaykh Hasan al-Banna, Sayyid Qutb, and Abul A'la al-Maududi are examined alongside modern interpretations. The findings indicate that the birth of the Islamic state represents a cultural revolution that integrates religious values with societal structures, as exemplified by the state of Medina. The study also highlights the state's function as the implementer of divine justice and social harmony. This research contributes to the discourse on the relationship between religion and state by emphasizing the necessity of an Islamic framework in political governance, while supporting the model of a moderate Islamic state compatible with pluralistic societies.